Variation in the isotopic composition of striped weakfish Cynoscion guatucupa of the Southwest Atlantic Ocean in response to dietary shifts - Paso Viola, María Natalia (2017)
The aim of this study was to analyze the isotopic composition in muscle of striped weakfish Cynoscion guatucupa from Southwest Atlantic Ocean in order to evaluate a possible variation in δ13C and δ15N in response to dietary shifts that occur as animals grow. We also explored for isotopic evidence of differences between sample locations. The results showed an agreement between isotope analysis and previous conventional studies. Differences in the isotope composition between sampling location were not observed. A positive relation exists between isotope values and total body length of the animals. The Cluster analysis defined three groups of size classes, validated by the MDS. Differences in the relative consumption of prey species in each size class were also observed performing isotope mixing models (SIAR). Variation in δ15N among size classes would be associated with the consumption of a different type of prey as animals grow. Small striped weakfish feed on small crustaceans and progressively increase their consumption of fish (anchovy, Engraulis anchoita), increasing by this way their isotope values. On the other hand, differences in δ13C values seemed to be related to age-class specific spatial distribution patterns. Therefore, large and small striped weakfish remain specialized but feeding on different prey at different trophic levels. These results contribute to the study of the diet of striped weakfish, improve the isotopic ecology models and highlight on the importance of accounting for variation in the isotopic composition in response to dietary shifts with the size of one of the most important fishery resources in the region.